FORMATION OF A UNIFIED REQUIREMENTS SYSTEM FOR ASSESSING THE SKILLS OF SPECIALISTS IN THE FIELD OF INNOVATION MANAGEMENT AS AN ESSENTIAL CONDITION FOR THE IMPLEMENTATION OF EFFECTIENT INNOVATION - M. A. Kosukhina (Дискурс)
The article is devoted to the problem of forming a unified requirements system for the assessment of specialists’ qualifications in the field of innovation management. The review and analysis of professional standards in the field of innovation activities in the Russian Federation is presented. The recommendations on usage the professional standards of related areas, such as: organization and management of research and development, risk management, information management in the framework of assessment of specialists qualifications in the field of innovation management allowing to consider the management of innovation activities in terms of digital economy and the knowledge economy development are provided. The foreign experience of application of professional standards in the field of innovative activity is investigated. The comparative analysis of foreign standards and standards operating in the territory of the Russian Federation is carried out, and the corresponding recommendations are offered.